RESULTS OF THE INTEGRATED ASSESSMENT OF THE POTENTIAL OF LIFESTYLE OF PATIENTS WITH ARTERIAL HYPERTENSION WITH DIFFERENT LEVEL OF TREATMENT PERFORMANCE - A. A. Gruzdeva; E. A. Kharitonova; E. A. Motyleva; M. V. Ilyin; D. L. Mushnikov (SINAPS LLC, 2018)
Introduction. Arterial hypertension is one of the most serious problems of the contemporary health care. Within the qualimetric approach and quantification of "lifestyle" capacity. However, research papers dealing with the relationship impact medical care cardiac profile and complete realization of the potential of the lifestyles of patients, it is not enough. The purpose of the research is to explore the potential lifestyle hypertensive patients and its role in ensuring the effectiveness of the treatment.Materials and methods. The study was conducted on the basis of the medical organizations of the Kostroma region. Research methods: expert, sociological, analytical, statistical. Analysed data on 400 patients a cardiac profile: lifestyle parameters monitoring data of patients using the original automated management factors impact medical care Cardiac profile, data expert evaluation of physician lifestyles of the patient and the patient questionnaire survey, consisting of 8 questions.Results and discussion. Found that in patients with arterial hypertension has reduced the capacity of lifestyle for all its components, including the low level of medical activity, low level of medical awareness, inadequate recreational activity disregard for the principles of a balanced diet, the prevalence of bad habits. There are significant differences in the potential lifestyle of patients with low and high levels of treatment success, proving the importance of lifestyle modification patients, his healing in the practice of primary care physicians health.Conclusions and proposals. It is recommended that the monitoring capacity of the lifestyles of patients with arterial hypertension in the context of district clinics.